The rice transcription factor OsWRKY47 is a positive regulator of the response to water deficit stress - Raineri, Jesica (2015)
OsWRKY47 is a divergent rice transcription factor belonging to the group II of the WRKY family. A transcriptomic analysis of the drought response of transgenic rice plants expressing PSARK::IPT, validated by qPCR, indicated that OsWRKY47 expression was induced under drought stress in PSARK::IPT plants. A PCR-assisted site selection assay (SELEX) of recombinant OsWRKY47 protein showed that the preferred sequence bound in vitro is (G/T)TTGACT. Bioinformatics analyses identified a number of gene targets of OsWRKY47; among these two genes encode a Calmodulin binding protein and a Cys-rich secretory protein. Using Oswrk47 knockout mutants and transgenic rice overexpressing OsWRKY47 we show that the transcription of these putative targets were regulated by OsWRKY47. Phenotypic analysis carried out with transgenic rice plants showed that Oswrky47 mutants displayed higher sensitivity to drought and reduced yield, while plants overexpressing OsWRKY47 were more tolerant.